HUBUNGAN MOTIVASI DENGAN KEMAMPUAN SERVIS BAWAH DALAM PERMAINAN BOLAVOLI - Nova Risma; Rices Jatra (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The problem in this study is the lack of activeness and motivation of students of SMP Negeri 6 Pekanbaru in the learning activities of volleyball games, especially in learning service below, so that learning activities do not run optimally. The purpose of this study was to determine the relationship of motivation with the ability to serve under the volleyball game of SMP Negeri 6 Pekanbaru students. This study is correlational that connects the independent variable, motivation (X) with the dependent variable, namely the ability to serve under the game of volleyball (Y). The population in this study were all students of SMP Negeri 6 Pekanbaru, totaling 335 people. The sampling technique in this study is Purposive Sampling, so that the students sampled in this study amounted to 54 people. Data collection for motivation is done by distributing questionnaires and service capabilities under Russel-Lange. The data obtained were analyzed using thecorrelation formula product moment with α = 0.05. Hypothesis test results show there is a relationship between motivation and the ability to service down in the game of volleyball (rxy = 0.345> rtable 0.281) and (tarithmetic = 2.520> ttable = 2.012). This means that the higher motivation possessed by SMP Negeri 6 Pekanbaru students, the tendency of lower service ability in volleyball games is also increasing. In another sense, the hypothesis is accepted (significant)